Catalytic Aerobic Oxidation and Tandem Enantioselective Cycloaddition in Cascade Multicomponent Synthesis. Issue 13 (11th February 2015) - Potowski, Marco; Merten, Christian; Antonchick, Andrey P.; Waldmann, Herbert
Abstract An efficient multicomponent cascade transformation for the highly diastereo‐ and enantioselective synthesis of complex natural product inspired polycyclic products from simple starting materials is described. The cascade is initiated by copper‐catalyzed aerobic CH oxidation of cyclopentadiene to cyclopentadienone followed by double catalytic asymmetric 1, 3‐dipolar cycloaddition of azomethine ylides. The cascade synthesis efficiently yields structurally complex 5, 5, 5‐tricyclic products with eight stereocenters with good yields and excellent diastereo‐ and enantiocontrol using one catalyst.